Green silver nanoparticles based on Lavandula coronopifolia aerial parts extract against mycotic mastitis in cattle. (July 2022) - Hasanin, Mohamed S.; Emam, Mahmoud; Soliman, Mona M.H.; Abdel Latif, Rasha R.; Salem, Maha M.M.; El Raey, Mohamed A.; Eisa, Wael H.
Abstract: The present study successfully investigated the green synthesis of silver nanoparticles (Ag NPs) using the methanolic extract of the aerial parts of Lavandula coronopifolia . The formation of Ag NPs was confirmed through color change as well as the UV/visible spectra. Further, characterizations were achieved using Fourier Transforms infrared spectroscopy (FT-IR), transmission electron microscope (TEM), thermal gravimetric analysis (TGA), and dynamic light scatting measurements (DLS). The collected isolates (twelve isolates) were identified microscopically as 8 Candida and 4 Aspergillus isolates. The Ag NPs exhibited excellent antifungal activity results against tested isolates compared with L. coronopifolia extract and the antifungal standard (Ketoconazole) with p  < 0.01. Ag NPs showed highly significant results towards C. albicans, C. tropicalis, A. fumigatus, and A. niger with MICs ranges of 1.7–0.7 μg/ml ( p  < 0.01). Depending on the stability and the effective diameters of the prepared Ag NPs using L. coronopifolia extract, it could be used as a simple, green preparation, eco-friendly, and low costs process that can be applied to the veterinary sector. Graphical abstract: Scheme (I): Illustrated the biosynthesis of Ag NPs using L. coronopifolia aerial parts against mycotic mastitis. Image 1 Highlights: Green Ag NPs based the extract of L. coronopifolia were prepared and characterized. Many functional groups of extract were used as capping agents to reduce Ag  +  to Ag 0 . Ag NPs manifested highly significant results against mycotic mastitis (cattle milk).